1975
DOI: 10.1111/j.1749-6632.1975.tb36019.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Function and Behavior: Defining the Relationship

Abstract: Over the years, this laboratory has studied radio-frequency (rf) energy effects, such as evoked potentials in the brains of cats, conditioned responses in cats and monkeys, frog heart arrhythmia, and hearing phenomena in cats and humans. A few years ago, one of us (A.H.F.) discussed the possible mechanisms by which rf energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 1 publication
0
48
1
Order By: Relevance
“…Since the first studies on the effect of microwave radiation on BBB of experimental animals [Polyaschuk, 1973;Frey et al, 1975], many investigators have reported on related studies with varied results. Microwave frequencies investigated range from 1 to 3 GHz.…”
Section: Blood Brain Barrier (Bbb) In Ratsmentioning
confidence: 98%
“…Since the first studies on the effect of microwave radiation on BBB of experimental animals [Polyaschuk, 1973;Frey et al, 1975], many investigators have reported on related studies with varied results. Microwave frequencies investigated range from 1 to 3 GHz.…”
Section: Blood Brain Barrier (Bbb) In Ratsmentioning
confidence: 98%
“…Prior to the start of the present project, certain compensatory thermoregulatory adjustments had been measured, including thermal adaptation (Michaelson et al, 1961), reduced metabolic heat production (Phillips et al, 1975;Ho and Edwards, 1977), and microwave avoidance (Frey et al, 1975). Few investigations into the consequences of microwave exposure on thermoregulatory behavior had appeared in the literature.…”
Section: The Problemmentioning
confidence: 99%
“…Other authors, however, stressed that the disturbance may occur under thermally controlled conditions [Frey et al, 1975;Oscar and Hawkins, 1977].…”
Section: Effects On Blood^brain Barrier Permeabilitymentioning
confidence: 96%